Case Based Reasoning untuk Klasifikasi Mutu Biji Buah Pala Kering - Deisya Maulida Al Hamid; Nelson Rumui; Syukron Anas (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Nutmeg (Myristica Fragnans) is a plant that has many benefits and is used in various industries. Indonesia is one of the world's largest producer and exporter of nutmeg seeds with a market share of 75 percent. Fakfak Regency is one of the largest nutmeg producing areas in Indonesia. There are 2 main categories, namely nutmeg with shell and nutmeg without shell. Nutmeg without shell has a high selling value because it has been processed where the shell from the nutmeg is separated from the seeds/contents/core from the nutmeg where there are 3 grades, namely grade 1 nutmeg ABCD, grade 2 Rimpel nutmeg, and grade 3 BWP nutmeg. The sorting process to select nutmeg seeds based on this grade is still carried out conservatively, namely by directly observing the nutmeg seeds one by one so that it takes time, effort and a large amount of money because it involves many workers, therefore a system is needed that can classify the quality of the seeds. Based on the grade of dried nutmeg, one of the expert systems that can accommodate the sorting process is Case-Based Reasoning. Based on the results of tests carried out using a confusion matrix, it shows that the system built has an overall accuracy of 90.5% and an overall system sensitivity of 71%.